2017
DOI: 10.1007/s11096-017-0505-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of common ailments requiring referral in the pharmacy: a mystery shopping intervention study

Abstract: Background Pharmacists can play a key role in managing ailments through their primary roles of supplying over-the-counter (non-prescription) medicines and advice-giving. It must be ensured that pharmacy staff practise in an evidence-based, guideline-compliant manner. To achieve this, mystery shopping can be used as an intervention to assess and train pharmacy staff. Objective To determine if repeated student pharmacist mystery shopping with immediate feedback affected the outcome of scenarios requiring referra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
3
19
0
11
Order By: Relevance
“…28 Collins and colleagues also showed a correlation between appropriate referral to a medical practitioner and the number of questions asked. 29 What we did however observe is that in pharmacy scenarios that ended in inappropriate advice, the number of questions was two or less. Perhaps the variation seen in the lack of correlation suggests that for different scenarios there are key questions that must be asked, rather than perhaps all questions.…”
Section: Discussionmentioning
confidence: 57%
“…28 Collins and colleagues also showed a correlation between appropriate referral to a medical practitioner and the number of questions asked. 29 What we did however observe is that in pharmacy scenarios that ended in inappropriate advice, the number of questions was two or less. Perhaps the variation seen in the lack of correlation suggests that for different scenarios there are key questions that must be asked, rather than perhaps all questions.…”
Section: Discussionmentioning
confidence: 57%
“…City Space Architecture / UN-Habitat Mystery shopping is a form of participant observation where the researcher interacts with the research participants being observed and stems from the field of cultural anthropology (Miller, 1998). The method is widely used in marketing (Miller, 1998, Collins et al, 2017, Yaoyuneyong et al, 2018 research and offers a possibility to identify different factors in the service delivery process (Jacob et al, 2018, Liu, 2015 and their effect on natural conditions (Grove and Fisk, 1992). It allows to test whether disabled consumers are treated equally or are discriminated against (Morrall, 1994, Wiele et al, 2005, Eskytė, 2019 and to address discrepancies between real and reported consumer and seller behaviour (Friedrichs et al, 1975, Kehagias et al, 2011.…”
Section: Mystery Shopping and Qualitative Interviewsmentioning
confidence: 99%
“…Jedną ze sprawdzonych metod oceny jakości usług w różnych obszarach, w tym związanych z ochroną zdrowia, są badania terenowe z wykorzystaniem metodologii tajemniczego/symulowanego pacjenta/klienta (tzw. mystery shopper/ mystery patient/simulated patient study) [15][16][17][18][19]. Jako tzw.…”
Section: Wstępunclassified
“…Doświadczenia z Australii wskazują, że implementacja takiego rozwiązania, tzw. protokół WHAT-STOP-GO (wchodzący w skład Australijskich Standardów dotyczących wydawania leków z aptek) powoduje, że ponad 60% konsultujących identyfikuje pacjenta i właściwie ocenia jego potrzeby lekowe [19]. Z uwagi na fakt, że w Polsce technicy farmaceutyczni i farmaceuci mają uprawnienia pozwalające im wydawać wszystkie preparaty dostępne bez recepty, wydaje się zasadne wdrożenie interwencji edukacyjnej kierowanej do obydwu grup zawodowych, dotyczącej potrzeby stosowania ww.…”
Section: Dyskusja Wynikówunclassified